Modeling a Decision Support System for Selection of Natural Stone Suppliers Using the Moora Algorithm - Muqorobin, Muqorobin; Efendi, Tino Feri (Institut Teknologi Bisnis AAS Indonesia, 2023)
Abstract—At SMK Negeri 1 Kismantoro, before this system was used, they only used manual methods or subjective, meaning the teacher still chooses students directly. The selection of outstanding students must be thorough used as a reference for the following year to ensure increased academic success. This competition was held Every year SMK Negeri 1 Kismantoro sends a team every year to advance in this competition. System Decision support can be made using several methods, one of which is the Moora method and Gain Ratio. This support system can assist in decision making in student selection achievement for the Kismantoro 1 State Vocational School competition. The operation of the Moore method consists of assigning weights on each criterion. The Increment Ratio method is used to find the criteria used in the Moora method that is, the highest value has 4 of the highest, that is, the card criteria is directly proportional to the gain of (0.44644), practice with a gain of (0.88129), attitude (personality) with a gain of (0.44644), skill with advantage (0.42836). The Moora method can select alternatives and rank them for make recommendations for the best students based on predetermined criteria which are Lutfiyatul Rosida's alternatives (A10) is the student who has the best performance with Yi-Max = 0.165.